2021
DOI: 10.1021/acsomega.0c05211
|View full text |Cite
|
Sign up to set email alerts
|

Assessing 1,9-Decadiene/Ethylene Copolymerization with Ziegler–Natta Catalyst to Access Long Chain-Branched Polyethylene

Abstract: 1,9-Decadiene/ethylene copolymerization is assessed as a way for Ziegler–Natta catalysts to access long chain-branched polyethylene (PE). A MgCl2/9,9-bis-(methoxymethyl)­fluorine/TiCl4 catalyst with triethylaluminium as a cocatalyst is exemplified for the task. 1,9-Decadiene was found to induce a substantial comonomer effect on catalyst activity and continuing decreases of PE molecular weight. Both the double bonds of 1,9-decadiene were poorly reactive during polymerization, of which the polymer chain-attached… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…[50] Beside advances in 𝛼,𝜔-dienes copolymerization using metallocene [47] and post-metallocene catalysts, [51] the production of LCB PP and PE via 𝛼,𝜔-dienes copolymerization using Ziegler-Natta catalysts (MgCl 2 /TiCl 4 ) has received great attention, due to the commercial dominance of Ziegler-Natta catalysts in PP and PE industry. [50,52] In this regard, there are several reports on using a variety of 𝛼,𝜔-diolefin like di-n-hexyldiethoxysilane, di-5-hexenyldiethoxysilane, di-5-hexenyldimethylsilane [53] and 1,9-decadiene. [50,52] Besides 𝛼,𝜔-dienes, Dong, and coworkers have reported on the incorporation of 𝜔-olefins difunctional comonomer, like 𝜔alkenylmethyldichlorosilane using Ziegler-Natta [53,54] and metallocene [55] catalytic systems for the synthesis of LCB PP.…”
Section: Direct Copolymerization With Difunctional Comonomersmentioning
confidence: 99%
“…[50] Beside advances in 𝛼,𝜔-dienes copolymerization using metallocene [47] and post-metallocene catalysts, [51] the production of LCB PP and PE via 𝛼,𝜔-dienes copolymerization using Ziegler-Natta catalysts (MgCl 2 /TiCl 4 ) has received great attention, due to the commercial dominance of Ziegler-Natta catalysts in PP and PE industry. [50,52] In this regard, there are several reports on using a variety of 𝛼,𝜔-diolefin like di-n-hexyldiethoxysilane, di-5-hexenyldiethoxysilane, di-5-hexenyldimethylsilane [53] and 1,9-decadiene. [50,52] Besides 𝛼,𝜔-dienes, Dong, and coworkers have reported on the incorporation of 𝜔-olefins difunctional comonomer, like 𝜔alkenylmethyldichlorosilane using Ziegler-Natta [53,54] and metallocene [55] catalytic systems for the synthesis of LCB PP.…”
Section: Direct Copolymerization With Difunctional Comonomersmentioning
confidence: 99%
“…[24] However, the silane protecting groups add greatly to the steric bulkiness of the comonomers, which is disfavored by the copolymerization as the catalysts in its effectiveness are highly sensitive to the steric hindrance of monomer. [25,26] In our recent practice of synthesizing long-chain-branched polypropylene (LCB-PP) with Ziegler-Natta catalysts involving copolymerization of propylene with 𝜔-alkenylmethyldichlorosilanes, we have found that due to the tri-substituted silane group the comonomers are much less favorable as compared to propylene. [27] Therefore, to increase the copolymerization efficiency, it becomes necessary to study the alkenyl length effect of the comonomers on their incorporation rates.…”
Section: Introductionmentioning
confidence: 99%
“…During the last three decades, metallocene-catalyzed ethylene/diene copolymerization has emerged as an efficient method towards post-functionalized- [1,2,3,4,5,6] and long-chain branched (LCB) polyethylene (PE) [7,8,9,10,11,12,13,14,15,16,17]. The latter aspect proved particularly interesting, since LCB-PEs most often exhibit significantly better processability than their linear counterparts, albeit retaining the excellent mechanical properties (i.e.…”
Section: Introductionmentioning
confidence: 99%